Some approaches to evaluation macroeconomic efficiency of digitalisation - Stremousova, Elena; Buchinskaia, Olga (Business, Management and Economics Engineering, 2019)
Purpose – the purpose of the article is to study the effect of digitalisation development indicators on per-capita GDP growth.Research methodology – the basic research method is the fixed-effects panel regression that describes the effect of the digitalisation development indicators on per-capita GDP between 1999 and 2017.Findings – research showed the most critical factors for per-capita GDP growth are the ones that linked with fixed and mobile subscriptions.Research limitations – The limitations of the research stem from the limitations of analysis as the method that has been employed makes it possible to measure the effect of the selected variables on per-capita GDP, but further research requires a detailed analysis of the factors being studied in application to each country.Practical implications – The findings can be used as a basis for choosing areas of more detailed factor analysis of the digitalisation process effectiveness and can support investment decision-making.Originality/Value – The study enables one to identify the most and the least important factors that are reflected by digitalisation indicators that have an impact on the per-capita GDP.